2015
DOI: 10.1063/1.4914549
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat and mass flux conditions in hydromagnetic flow of Jeffrey nanofluid

Abstract: This article explores the hydromagnetic steady flow of Jeffrey fluid in the presence of thermal radiation. The chosen nanofluid model takes into account the Brownian motion and thermophoresis effects. Flow and heat transfer characteristics are determined by a stretching surface with flux conditions. The nonlinear boundary layer flow through partial differential systems is converted into the ordinary differential systems. The resulting reduced systems are computed for the convergent solutions of velocity, tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 28 publications
(28 reference statements)
3
31
0
Order By: Relevance
“…Crane [1] initiated a study on steady boundary layer flow of a Newtonian fluid over a stretching sheet which is movable in its own plane and velocity varying linearly with the distance measured from a fixed point where the uniform stress is applied. A considerable amount of attention has been drawn in the study of boundary layer flow over a stretching sheet [2][3][4][5][6][7][8][9] in the presence/absence of magnetic field. Many experimental and theoretical studies have been undertaken in past by considering conventional electrically conducting fluids in the presence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Crane [1] initiated a study on steady boundary layer flow of a Newtonian fluid over a stretching sheet which is movable in its own plane and velocity varying linearly with the distance measured from a fixed point where the uniform stress is applied. A considerable amount of attention has been drawn in the study of boundary layer flow over a stretching sheet [2][3][4][5][6][7][8][9] in the presence/absence of magnetic field. Many experimental and theoretical studies have been undertaken in past by considering conventional electrically conducting fluids in the presence of magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…More works on parametric studies of the ow process can be found in [26][27][28][29][30][31][32][33][34]. Additionally, analyses of magnetohydrodynamic ow in the porous medium have been presented in various works [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] while various studies of magneto-nano uid ow have also been presented in the past works [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68].…”
Section: Introductionmentioning
confidence: 99%
“…This fluid model exhibits the properties of ratio of relaxation to retardation times and retardation time. Few attempts about Jeffrey fluid model are mentioned in the studies by Kothandapani and Srinivas (2008), Tripathi et al (2011), Hayat et al (2012), Abbasi et al (2015) and Farooq et al (2015).…”
Section: Introductionmentioning
confidence: 99%